Folic acid intake and folate status and colorectal cancer risk: A systematic review and meta-analysis - Moazzen, Sara; Dolatkhah, Roya; Tabrizi, Jafar Sadegh; Shaarbafi, Jabraeel; Alizadeh, Behrooz Z.; de Bock, Geertruida H.; Dastgiri, Saeed (Clinical nutrition (Edinburgh, Scotland), 2018)
To evaluate the controversies among the studies assessing the association between folic acid intake or folate status and colorectal cancer risk. PubMed, Cochrane library and references of related articles were searched from January 2000 to September 2016. Studies on folic acid intake or folate status and colorectal cancer or adenoma risk were included. Full text review was conducted for potentially eligible studies. Quality assessment was performed. Random-effects meta-analysis was used to estimate risk ratio and 95% Confidence Intervals. Analysis was conducted by Comprehensive Meta-Analysis software. Folic acid supplement intake showed no significant effect on colorectal cancer risk in meta-analysis of randomized controlled trials, RR: 1.07 (95% CI: 0.86–1.43). The effect on risk was not significant in cohort studies either; RR = 0.96 (95% CI: 0.76–1.21). However, there was significant reduced colorectal cancer risk in total folate intake in cohort studies; 0.71 (95% CI: 0.59–0.86). Odds Ratio was also significantly reduced in case control studies; 0.77 (95% CI: 0.62–0.95). Nevertheless once folate status was measured as Red Blood Cell folate content, no significant effect on colorectal cancer risk was observed; 1.05 (95% CI: 0.85–1.30). The differences in bioavailability and metabolism of synthetic folic acid and natural dietary folate as well as variation in the baseline characteristics of subjects and various methods of folate status assessment might be the main reasons for these controversies. Findings of present study highlight the importance of individualized folic acid supplement intake given the fact that the beneficiary effects of long term folic acid supplementation is not confirmed.